Biofunctionalized polymer interfaces for capture, isolation, and characterization of bacteria - Masigol, Mohammadali (Kansas State University, 2020)
The goal of this research is to develop bio-functional interfaces, designed using polymeric materials, for improved separation and isolation of bacteria for detection and characterization. Microbes impact many aspects of our society, from health to environment to industrial processes. In most cases, microbes exist in complex environments, where thousands of other organisms may also be present. Thus, detecting and characterizing specific microbial targets often necessitates that they are first isolated. Polymeric materials hold several advantages for this type of separation. They can be modified with biomolecules to capture specific microorganisms and can be designed to release captured organisms on-demand using an environmental stimulus. This thesis will explore each of these concepts, beginning with (1) the design of patterned polymer interfaces to tailor the surface reactivity towards biomolecules, (2) bio-functionalization of surface polymers with lectin molecules for bacteria capture, and (3) bio-functional, photodegradable hydrogels for dissection of microbes from membrane surfaces during early-stage biofouling events. The first portion of this thesis aims at fabricating micro/nano-structured patterns of the novel block co-polymer, poly(glycidyl methacrylate)–block–poly(vinyl dimethyl azlactone) (PGMA₅₆-b-PVDMA₁₇₅) onto silicon slides. These polymers use azlactone-based reactions to covalently couple biomolecules to the surface. Bottom-up and top-down chemical co-patterning methods, including microcontact printing, parylene lift-off, and interface directed assembly are investigated for formation of reproducible, brush-like and crosslinked polymers on the substrates. The second portion of this thesis uses these polymer interfaces to capture microbial contaminants from solution using lectin-based binding. Lectin-functionalized interfaces are promising for affinity-based microorganism capture and isolation of bacteria from samples such as blood, urine, and wastewater. However, the equilibrium dissociation constants (K[subscript]D) of lectin-carbohydrate interactions, 2-3 orders of magnitude higher than antibody-antigen binding constants, results in poor cell capture efficiency. To address this limitation, surfaces are designed to combine reactive polymer coatings that generate high lectin surface densities with nanoscale surface structures, ultimately improving cell capture. Both detection sensitivity and bactericidal impact of these optimized surfaces are characterized. Finally, the competing effects on capture due to lectin surface density and due to exopolysaccharide expression levels on the bacteria cell surface is compared. The final portion of this thesis focuses on the use of lectin-functionalized, photodegradable hydrogels to separate and isolate microbes that attach to membrane surfaces during early-stage biofouling, an approach termed polymer surface dissection (PSD). Photo-responsive, biofunctional polyethylene glycol (PEG)-based hydrogels are developed to detach targeted biofilm flocs or cells adhered onto PVDF membranes. A patterned illumination tool then delivers light to the hydrogel in a spatiotemporally controlled manner to release an extracted floc without damage. Microbes can then be sequenced to identify the composition of biofilm flocs at different stages of aggregation. The PSD approach can be used to characterize biofouling in many membrane-based bioseparation processes, here it has been developed to investigate membrane biofouling in anaerobic membrane bioreactors. Understanding the initial stages of biofouling from a mechanistic standpoint could help understand the critical microorganisms in wastewater communities that initiate the biofouling process, information that can inform novel techniques to mitigate biofilm formation.
Keywords: Biofunctional polymers; Polymer patterning; Lectin-functional interfaces; Bacterial capture; Biofouling characterization; Polymer surface dissection